CO2 electrolysis to multi-carbon products in strong acid at ampere-current levels on La-Cu spheres with channels - Feng, Jiaqi; Wu, Limin; Song, Xinning; Zhang, Libing; Jia, Shunhan; Ma, Xiaodong; Tan, Xingxing; Kang, Xinchen; Zhu, Qinggong; Sun, Xiaofu; Han, Buxing (Nature communications, 2024)
Achieving satisfactory multi-carbon (C 2+ ) products selectivity and current density under acidic condition is a key issue for practical application of electrochemical CO 2 reduction reaction (CO 2 RR), but is challenging. Herein, we demonstrate that combining microenvironment modulation by porous channel structure and intrinsic catalytic activity enhancement via doping effect could promote efficient CO 2 RR toward C 2+ products in acidic electrolyte (pH ≤ 1). The La-doped Cu hollow sphere with channels exhibits a C 2+ products Faradaic efficiency (FE) of 86.2% with a partial current density of −775.8 mA cm −2 . CO 2 single-pass conversion efficiency for C 2+ products can reach 52.8% at −900 mA cm −2 . Moreover, the catalyst still maintains a high C 2+ FE of 81.3% at −1 A cm −2 . The channel structure plays a crucial role in accumulating K + and OH - species near the catalyst surface and within the channels, which effectively suppresses the undesired hydrogen evolution and promotes C–C coupling. Additionally, the La doping enhances the generation of *CO intermediate, and also facilitates C 2+ products formation. Efficient electroreduction of CO2 to multi-carbon products under strong acidic condition is highly challenging. Here, the authors demonstrate that combining microenvironment modulation and La doping effect could promote multicarbon products generation in acidic electrolyte.